Cinobufagin inhibits proliferation of acute myeloid leukaemia cells by repressing c-Myc pathway-associated genes. (1st June 2022) - Hirasaki, Yoshiro; Okabe, Atsushi; Fukuyo, Masaki; Rahmutulla, Bahityar; Mano, Yasunobu; Seki, Motoaki; Hoshii, Takayuki; Namiki, Takao; Kaneda, Atsushi
Abstract: Cinobufagin is a cardiotoxic bufanolide steroid secreted by the Asiatic toad, Bufo gargarizans . Bufanolides inhibit Na + /K + ATPase and have similar effects as cardiac glycosides, such as digitoxin or ouabain derived from toxic herbs. Recently, the anti-cancer effects of bufanolides have gained attention, however the underlying molecular mechanisms remain unclear. Selecting cinobufagin as a candidate anti-leukaemia agent, we here conducted transcriptomic analyses on the effect of cinobufagin on human acute myeloid leukaemia (AML) cell lines, HL60 and Kasumi-1. Flow cytometry analysis showed that cinobufagin induced apoptosis in both cell lines. RNA-sequencing (RNA-seq) of the two cell lines treated with cinobufagin revealed commonly downregulated genes with enrichment in the term "Myc active pathway" according to Gene Ontology (GO) analysis. Gene Set Enrichment Analysis (GSEA) of genes downregulated by cinobufagin also showed "MYC_TARGETS_V2" with the highest normalised enrichment score (NES) in both cell lines. In contrast, hallmarks such as "TNFA_SIGNALING_VIA_NFKB", "APOPTOSIS", and "TGF_BETA_SIGNALING" were significantly enriched as upregulated gene sets. Epigenetic analysis using chromatin immunoprecipitation and sequencing (ChIP-seq) confirmed that genes encoding cell death-related signalling molecules were upregulated by gain of H3K27ac, whereas downregulation of c-Myc-related genes was not accompanied by H3K27ac alteration. Cinobufagin is an anti-proliferative natural compound with c-Myc-inhibiting and epigenetic-modulating activity in acute myeloid leukaemia. Graphical abstract: Image 1 Highlights: Cinobufagin inhibits acute myeloid leukaemia cell proliferation. c-Myc and its target genes were repressed by cinobufagin. Cinobufagin showed epigenetic-modulating activity. AP1 and RUNX1 are critical transcription factors in cell signals leading to cell death.